Antibacterial Activity of Endophytic Fungi Isolated from Turmeric Plants (Curcuma longa L.) Against Staphylococcus aureus and Escherichia coli - Irvanita, Deva Anggun; Rohmantin, Dita; Adz-Dzikir, Fatihatuljannah; Sari, Tri Puspita; Jinan, Rifa Fatma; Aji, Oktira Roka (Journal of Biotechnology and Natural Science, 2024)
Endophytic fungi are fungi that live in a mutualistic relationship with their hosts. They can produce secondary metabolites that are similar to the host plant. Turmeric plants (Curcuma longa L) are highly valued for their medicinal properties and contain active compounds in their rhizomes that act as antibacterials. This study aimed to measure the inhibitory effect of endophytic fungi from turmeric rhizomes against the growth of two bacteria, Escherichia coli and Staphylococcus aureus. The study involved isolating fungi, observing macroscopic and microscopic morphology, and testing the antibacterial activity of turmeric endophytic fungi against E. coli and S. aureus. A type of endophytic fungi was successfully isolated from the turmeric plant. The morphological characteristics of the endophytic fungi from turmeric plants include a white colour with a cotton-like texture, umbonate topography, radial lines, and concentric circles. In contrast, the microscopic characteristics include septate hyphae and conidia. Turmeric endophytic fungi were found to inhibit both pathogenic bacteria with inhibition zones of 19.25 mm (strong) against E. coli and 13.75 mm (strong) against S. aureus. In conclusion, this study successfully isolated endophytic fungi from turmeric plants that can inhibit the growth of E. coli and S. aureus. However, further identification of the strain and activity tests is necessary to determine the effectiveness of the bioactive compounds in inhibiting the growth of bacteria.